2016
DOI: 10.5935/abc.20160204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Normality Thresholds for 24-hour ABPM at the Primary Health Care Level

Abstract: BackgroundHypertension is an important risk factor for cardiovascular outcomes. Primary health care (PHC) physicians should be prepared to act appropriately in the prevention of cardiovascular risk factors. However, the rates of patients with control of blood pressure (BP) remain low. The impact of the reclassification of high BP by 24-hour ambulatory BP monitoring (ABPM) can lead to different medical decisions in PHC.ObjectiveTo evaluate the agreement between the BP measured by a conventional method by PHC ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…[15][16][17] This process requires the involvement of a multidisciplinary team and more specific tests that determine the diagnosis and then the appropriate therapy for the clinical condition of each individual, in an equitable and resolving way. 5,[19][20] Given the fact that the procedures are revealed expensive and even time-consuming, as the patient needs to return to health services several times, it is suggested that it is of utmost importance that the user be guided about the flow of the diagnosis and fully comply with all stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] This process requires the involvement of a multidisciplinary team and more specific tests that determine the diagnosis and then the appropriate therapy for the clinical condition of each individual, in an equitable and resolving way. 5,[19][20] Given the fact that the procedures are revealed expensive and even time-consuming, as the patient needs to return to health services several times, it is suggested that it is of utmost importance that the user be guided about the flow of the diagnosis and fully comply with all stages.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22] The MAP contributes to the assertive decision making by the team, reduces the need for excessive returns to the unit, optimizes the coordination of customer care in the Health Care Network of the municipalities and reduces the occurrence of events related to cardiovascular risks. [20][21] As for the accessibility indicator related to "waiting for the medical appointment", despite not having a significant association as a factor that influences the demand for other services without PHC characteristics, it is conjectured that this is one of the difficulties of the healthcare system, due to low resolution, formation of waiting lines, among others of organizational origin, which contribute to the evasion of users of the services offered by PHC. 22 In this regard, a study carried out in Belo Horizonte, with the objective of evaluating the indicators of use and quality of the services offered by the PHC, pointed out better evaluations for those who regularly use the services, but anchored with supplementary health plans, as they had access to exams faster, differentiating themselves from those who used only SUS and who evaluated negatively.…”
Section: Discussionmentioning
confidence: 99%
“…This implies, from a practical perspective, that whenever ABPM is not available or is difficult to access, at least part of its advantages can nevertheless be obtained either through the use of home BP self‐monitoring (recently further improved by the current availability of devices with nocturnal BP monitoring function) or through an increase in the number of automated readings which can be obtained by repeating BP measurements both within visits and over repeated visits, and then averaged . However, even in developed countries the use of ABPM is at present still recommended in selected cases only, although indications for ABPM are becoming progressively wider, based on the evidence that a larger use of ABPM could contribute to reduce health care cost, prevent cardiovascular events, and be life‐saving …”
Section: Historical Perspectivementioning
confidence: 99%
“…WFI data is used as the main data source of ecological remote sensing image data of vegetation destruction in waterfront greenway (Grezzana et al 2017). WFI data are remote sensing wide field of view data obtained by WFI sensors on CBERS02B satellite, CBERS02 satellite, CBERS01 satellite and Landsat5 satellite, including CCD data and TM data (Kang et al 2018), (Govindan and Annamalai, 2019).…”
Section: Acquisition Of Ecological Remote Sensing Image Datamentioning
confidence: 99%